2016
DOI: 10.1177/1468087416665052
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic model for homogeneous charge compression ignition combustion with recompression valve events and direct injection: Part II—Combustion model and evaluation against transient experiments

Abstract: This two-part article presents a combustion model for boosted and moderately stratified homogeneous charge compression ignition combustion for use in thermodynamic engine cycle simulations. The model consists of two parts: one an ignition model for the prediction of auto-ignition onset and the other an empirical combustion rate model. This article focuses on the development of the combustion model which is algebraic in form and is based on the key physical variables affecting the combustion process. The model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The accompanying article 44 presents an empirical combustion duration correlation and shows that if the ignition timing is accurately provided, the rest of the combustion profile is well matched to the experiments. The ignition model and burn correlation are implemented into GT-Power and the model is exercised at each of the experimental operating conditions in a manner similar to the TPA process.…”
Section: Ignition Model Tuning and Validationmentioning
confidence: 87%
See 2 more Smart Citations
“…The accompanying article 44 presents an empirical combustion duration correlation and shows that if the ignition timing is accurately provided, the rest of the combustion profile is well matched to the experiments. The ignition model and burn correlation are implemented into GT-Power and the model is exercised at each of the experimental operating conditions in a manner similar to the TPA process.…”
Section: Ignition Model Tuning and Validationmentioning
confidence: 87%
“…engine experiments, which are also used to develop and validate the combustion profile model in the companion article. 44 The experiments were performed on a modified dual variable valve timing (VVT), spark ignited direct ignition (SIDI) 2010 GM Ecotec 2.0L engine. The engine specifications are provided in Table 10.…”
Section: Engine Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…It must be noted that chemistry during NVO is ignored. Shingne 34 has shown that reactions during NVO can change the temperature and composition of the charge. However, Olesky et al 32 show in their experimental study that early combustion phasing, similar to current simulations, lead to high combustion efficiency and little NVO heat release due to unburned fuel.…”
Section: Open-cycle Cfd Simulationsmentioning
confidence: 99%
“…12 Multi-cycle computational fluid dynamics (CFD) models have also been used to show this effect and have determined that the remaining fuel and intermediate species from the previous cycle can lead to combustion during the negative valve overlap (NVO) recompression and an early combustion phasing in the following cycle. 13…”
Section: Introductionmentioning
confidence: 99%